Heidegger and the Hermeneutics of Serenity (Gelassenheit) - Martin De Blassi, Fernando Gabriel (Revista de Humanidades de Valparaíso, 2022)
This paper aims to review the meaning and scope of the Heideggerian notion of serenity. In accordance with this purpose, the research is articulated according to four thematic units that allow reconstructing and synoptically exposing the most significant aspects that Heidegger elucidates throughout his conference, given in 1955 with the title of Gelassenheit. These points read as follows: (1) the meaning and semantic scope of the word serenity; (2) the condition of autochthony and the threatening nature of calculating thought; (3) technique, violence and alienation; (4) the Heideggerian sense of serenity according to the meaning of equanimity. For the interpretation of the documents, the methodology commonly used in studies concerning the history of philosophy is adopted, which consists of a hermeneutical and critical reading of the texts selected for analysis, together with the unavoidable support favored by the specialized bibliography.